Satellite images as tools of visual diplomacy: NASA's ozone hole visualizations and the Montreal Protocol negotiations - Grevsmühl, Sebastian; Briday, Régis (The British Journal for the History of Science, 2023)
International audience On 16 September 1987, the main chlorofluorocarbon-producing and -consuming countries signed the Montreal Protocol, despite the absence of a scientific consensus on the mechanisms of ozone depletion over Antarctica. We argue in this article that the rapid diffusion from late 1985 onwards of satellite images showing the Antarctic ozone hole played a significant role in this diplomatic outcome. Whereas negotiators claimed that they chose to deliberately ignore the Antarctic ozone hole during the negotiations since no theory was able yet to explain it, the images still loomed large for many of the actors involved. In Western countries, the National Aeronautics and Space Administration's (NASA) satellite visualizations were diffused through the general press and television stations. Other popular and mass media outlets followed quickly. In describing the circulation and appropriation processes of these images within and beyond the scientific and negotiation arenas, we show that the ozone hole images did play an important part in ozone diplomacy in the two years leading up to the signing of the Montreal Protocol, both in the expert and diplomatic arenas and as public diplomacy tools. We conclude by encouraging scholars to engage with new visual archives and to contribute to the development of the vibrant new field of research on visual diplomacy.